2003
DOI: 10.1103/physreve.67.061403
|View full text |Cite
|
Sign up to set email alerts
|

Aging and nonlinear rheology in suspensions of polyethylene oxide–protected silica particles

Abstract: In an attempt to establish connections between classical rheology and aging in paste colloidal suspensions, we report in this paper a large set of experimental results on a given system. We have studied suspensions of polyethylene oxide-protected silica particles and performed classical rheology experiments that exhibit a very nonlinear behavior. We have then evidenced aging through stress relaxation as observed in various glassy systems, and finally show other manifestations of aging through various rheologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
163
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(182 citation statements)
references
References 24 publications
18
163
1
Order By: Relevance
“…This results in an evolution of the properties of the system with time, a phenomenon commonly referred to as aging. The aging dynamics exhibited by soft glasses is strongly influenced by the deformation field [13][14][15][16][17]. Sollich et al [1] proposed that the application of strain enhances the potential energy of the trapped particle, and if the barrier height (or yield energy) of the energy well is exceeded, the particle escapes the well (or cage) and an yielding event occurs.…”
Section: Introductionmentioning
confidence: 99%
“…This results in an evolution of the properties of the system with time, a phenomenon commonly referred to as aging. The aging dynamics exhibited by soft glasses is strongly influenced by the deformation field [13][14][15][16][17]. Sollich et al [1] proposed that the application of strain enhances the potential energy of the trapped particle, and if the barrier height (or yield energy) of the energy well is exceeded, the particle escapes the well (or cage) and an yielding event occurs.…”
Section: Introductionmentioning
confidence: 99%
“…The direct visualization of local plastic events and the associated complex avalanching dynamics is supported by many experimental [11][12][13][14] or numerical [15][16][17] studies. In the "solid phase" corresponding to a strong dynamical arrest, soft-glassy systems display ageing properties manifesting in a slow creep relaxation process [18][19][20][21]. Ageing properties stem from a remaining thermal activation providing the possibility to cross enthalpic or entropic barriers and progressively set the system into deeper local minima where mechanical solidity is reinforced.…”
mentioning
confidence: 99%
“…In order to demonstrate simply how this mechanism works, we build on the macroscopic rheological model proposed by Derec et al [10] to understand the rheology of soft glassy materials. This model was used to analyse ageing and nonlinear rheology of pastes [19] and also creeping processes in granular matter [13,20,30]. This generic model introduces a macroscopic phenomenological variable, the fluidity defined as the inverse time scale characterizing the material visco-elastic response.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in experiments spanning wide differences in cellular interventions, cell type, and even integrative scale, we have shown that these physical events conform to common scaling relationships and thereby suggest a universal class of responses (12). Dynamics of a closely similar kind have been reported in inert glassy materials such as those alluded to previously, all of which are soft, structurally disordered, and systematically displaced away from thermodynamic equilibrium (46)(47)(48)(49)(50)(51)(52)(53)(54)(55). Indeed, in the recent 125th anniversary issue of Science focused on ''What we don't know,'' the dynamics of glassy systems was highlighted as being one of the 125 greatest unsolved problems in all of science (16).…”
Section: The Asthmatic Attack As a Cytoskeletal Glass Transition?mentioning
confidence: 73%